Room temperature excitation spectroscopy of single quantum dots - Christian Blum; Frank Schleifenbaum; Martijn Stopel; Sébastien Peter; Marcus Sackrow; Vinod Subramaniam; Alfred J. Meixner (Beilstein Journal of Nanotechnology, 2011)
We report a single molecule detection scheme to investigate excitation spectra of single emitters at room temperature. We demonstrate the potential of single emitter photoluminescence excitation spectroscopy by recording excitation spectra of single CdSe nanocrystals over a wide spectral range of 100 nm. The spectra exhibit emission intermittency, characteristic of single emitters. We observe large variations in the spectra close to the band edge, which represent the individual heterogeneity of the observed quantum dots. We also find specific excitation wavelengths for which the single quantum dots analyzed show an increased propensity for a transition to a long-lived dark state. We expect that the additional capability of recording excitation spectra at room temperature from single emitters will enable insights into the photophysics of emitters that so far have remained inaccessible.